2018
DOI: 10.1111/bjep.12237
|View full text |Cite
|
Sign up to set email alerts
|

The role of within‐class consensus on mastery goal structures in predicting socio‐emotional outcomes

Abstract: Our findings show that higher levels of within-class consensus on mastery goal structures enhance beneficial socio-emotional outcomes. Moreover, the results emphasize the value of expanding the scope of educational research to the study of within-class consensus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
0
17
0
2
Order By: Relevance
“…Finally, we restricted our focus in terms of predictors of dropout intentions to contextrelated problems and PB goals. Although the choice of these two predictors was theoretically justified and empirically supported by the study's findings, further research is encouraged to examine the effects of other contextual characteristics, such as institutional culture or motivational climate (e.g., Skaalvik and Skaalvik 2013;Bardach et al 2019a;Bardach 2019b), and other individual characteristics. With regard to individual characteristics, it might be particularly illuminating to expand the scope to specific personality traits, such as self-compassion (e.g., Patzak et al 2017), or motivational facets not yet considered in research on university dropout, such as implicit theories or achievement goals (e.g., Bardach et al 2019c;Darnon et al 2018).…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 94%
“…Finally, we restricted our focus in terms of predictors of dropout intentions to contextrelated problems and PB goals. Although the choice of these two predictors was theoretically justified and empirically supported by the study's findings, further research is encouraged to examine the effects of other contextual characteristics, such as institutional culture or motivational climate (e.g., Skaalvik and Skaalvik 2013;Bardach et al 2019a;Bardach 2019b), and other individual characteristics. With regard to individual characteristics, it might be particularly illuminating to expand the scope to specific personality traits, such as self-compassion (e.g., Patzak et al 2017), or motivational facets not yet considered in research on university dropout, such as implicit theories or achievement goals (e.g., Bardach et al 2019c;Darnon et al 2018).…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 94%
“…This model can serve as the theoretical rationale guiding future empirical research for investigating the antecedents of student perception variability of teaching quality. Also, the model can be used to understand the universal reasoning behind the empirical research that investigates the consequences of student perception variability (e.g., Schweig, 2016 ; Schenke et al, 2017 ; Bardach et al, 2019a ). Empirical research reported that lower levels of student variability are associated with better learning outcomes.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In this sense, there are important coincidences between what is conceived as an interactional context and what is now understood as classroom climate, focusing on the social environment where interaction is happening in the educational space [13][14][15]. Different authors define classroom climate as a general concept that groups together factors such as the quality of interactions, their fluidity in complex situations involving environmental and social factors and the characteristics that indicate their condition or state, usually from a community perspective [16,17].…”
Section: Theoretical Framework 21 Emotions and Learningmentioning
confidence: 99%